Translanguaging in Youtube Channel: A Case Study of Nessie Judge - Permadi, Mandala Erlangga Indra; Yusra, Kamaludin; Isnaini, Muh.; Mahyuni, Mahyuni (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2023)
This study aims at describing the components of translanguaging, the reason for using translanguaging, and the functions of translanguaging in YouTube videos. This research used the descriptive qualitative method. The data were collected from the YouTube channel of Nessie Judge. First, the researcher was transcribed the utterances into written text. Then, identified the transcript and classified into each components of translanguaging. After that, reduced data in the form of table. The components are divided according to the utterances. Then, the researcher was interpreted the reasons of translanguaging in Nessie Judge’s YouTube videos. In addition, the researcher was found the speech function of translanguaging used by Nessie Judge in her YouTube videos. The results of this study show there are two components of translanguaging that Nessie used in her YouTube videos. The translanguaging’s components used in the three videos were dominated by 83% code-switching, and 17% translating and interpreting. The difference between translanguaging and code switching lies in the concept. The concept of translanguaging gives freedom for anyone to use more than two languages without any restrictions, while code-switching has its own limitations. The result of this study also finds there are six reasons why Nessie Judge used translanguaging. The most dominant reason of Nessie Judge used translanguaging is talking about a particular topic with 78%. In addition, there are five speech functions Nessie Judge used translanguaging. The most dominant speech function of Nessie Judge used in the three videos is 74% metalinguistic function.